Hubungan Pemberian ASI dan Tingkat Pendidikan Ibu dengan Status Gizi 1000 Hari Pertama Kehidupan - Aulia Nur Rokhmah; Burhanuddin Ichsan; Tri Agustina; Muhammad Shoim Dasuki (Universitas Muhammadiyah Klaten, 2021)
The period of the first 1000 days of life is a very important period for the improvement of nutrition and growth and development of children. The 2018 Kebumen District Health Profile states that 8% of toddlers with malnutrition, 33.05% of toddlers who do not get exclusive breastfeeding, and mothers of toddlers with malnutrition are mostly 60% primary school education, 20% junior high school and 20% high school education. . To analyze the relationship between exclusive breastfeeding and mother's education with the nutritional status of children under five in the first 1000 days of life. This research is an analytic observational study with a case control design. The instrument used in this study is secondary data by taking samples using purposive sampling technique as many as 117 samples at the Petanahan Health Center. In the bivariate analysis of Chi Square test, it was found that the ASI variable showed p value = 0.000 with OR = 21.991 and mother's education showed p = 0.000 with OR = 6.279. There is a relationship between exclusive breastfeeding and mother's education with the nutritional status of toddlers in the first 1000 days of life.